Design and synthesis of 2-amino-thiophene-tethered ureidopenicillin analogs with potentantibacterial and antitubercular activity - Wagh, Mahendra A.; Baravkar, Sachin B.; Jedhe, Ganesh S.; Borkute, Rachna; Choudhari, Amit S.; Sarkar, Dhiman; Sanjayan, Gangadhar J. (ChemistrySelect, 2018)
Ureidopenicillins are a class of penicillins which are antibiotics active against gram-negative bacteria. Herein, we report the synthesis of 2-aminothiophene-tethered ureidopenicillin analogues and their in vitro antibacterial and antitubercular activity. Intriguingly, unlike the reported ureidopenicillins which are active against gram-negative bacteria, the synthesised 2-aminothiophene-tethered ureidopenicillins were significantly active against Gram-positive bacterial strains and showed moderate inhibition towards gram-negative bacterial strains. Among all the analogs, compound 1b containing 2-aminothiophene moiety with minimum inhibitory concentration (MIC): 0.29, 0.32, > 10, > 10 mg/ml for Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa, respectively, showed better anti-bacterial profile as compared to cephalexin and equipotent to ampicillin and amoxicillin on gram-positive bacterial strains. All the derivatives were also screened for anti-TB activity against mycobacterium tuberculosis H37Ra. Among the series, cycloocta-thiophene-tethered cephalexin analog 3c displayed excellent antitubercular activity with MIC values 0.78 mg/ml. Low cytotoxicity and high selectivity index indicate the efficacy of 3c against mycobacterial infections. The results from present study offer a novel approach to modify the existing drug class of ureidopenicillins to yield antimicrobials with promising utility.

Synthesis and anticancer activity of conformationally constrained Smac mimetics containing pseudo beta turns - Baravkar, Sachin B.; Wagh, Mahendra A.; Paul, Debasish; Santra, Manas; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2018)
Herein, we report synthesis and in vitro anticancer activity of conformationally constrained Smac mimetics containing reverse turn inducing motifs "Ant-Pro" and "sAnt-Pro". The synthesis of Smac analogs with diverse hydrophobic groups at the C-terminus was carried out using solution phase peptide synthesis. The synthesis of Ant-Pro containing analogs 3a-j was carried out by ring opening of benzoxazinones 7a-c, whereas, their sulfonamide counterparts 4a-h were synthesized by using routine acid-amine coupling reaction. In vitro anticancer studies against breast cancer cell line MDA-MB-231 revealed that some of the new analogs had better anticancer activity than the standard AVPI Smac tetrapeptide. (C) 2018 Published by Elsevier Ltd.

Design and synthesis of 2-amino-thiophene-proline-conjugates and their anti-tubercular activity against mycobacterium tuberculosis H37Ra - Baravkar, Sachin B.; Wagh, Mahendra A.; Nawale, Laxman U.; Choudhari, Amit S.; Bhansali, Sujit; Sarkar, Dhiman; Sanjayan, Gangadhar J. (ChemistrySelect, 2019)
The emergence of extensively drug resistant tuberculosis (XDRTB) and multi-drug resistant tuberculosis (MDR-TB) has necessitated the development of new drugs with short chemotherapy treatment regime and cost effectiveness. To overcome these challenges, we are reporting the synthesis of a series of 2-amino-thiophene-proline-conjugates which show potent invino and ex-vivo anti-tubercular (anti-TB) activity against mycobacterium tuberculosis (rntb) H37Ra. The synthesis of these 2-amino-thiophene-proline-conjugates was carried out via solution phase peptide coupling reactions using methyl-2aminothiophene-3-carboxylate 8 as an intermediate obtained by modified gewald reaction. Intermediate 8 was coupled with different amino acids to obtain dipeptides 3, 4, 5, 6a and 7. Priliminary anti-TB assay data encoureaged us to synthesize modified proline derivatives 6b-6k via formation of a benzoxazinone intermediate 16. Most of these conjugates are active against mtb H37Ra in both active (A) and dormant (D) strains. They are also active against drug resistant mtb H37Ra strains. A trifluoroethyl ester analog, 6i was the most potent among the series [MIC 1 mu g/mL] along with 6f and 6g [MIC 2-6 mu g/mL]. Cytotoxicity studies suggested that, these compounds are less cytotoxic to human cell lines HeLa, MCF-7, HUVEC and hence possess high selectivity index (SI). Docking studies revealed that the binding mode of most active compounds 6i, 6g and 6f is in accordance with their bioactivity studies having docking score 8.969, 8.446 and 7.865, respectively. More- over, in sllico ADME properties suggest that all the compounds possess drug like properties.
Keywords: 2-aminothiophene; Anti-tubercular; docking studies; Inh A gene; selectivity index

Three in one: triple G-C-T base-coded brahma nucleobase amino acid: synthesis, peptide formation, and structural features - Wagh, Mahendra A.; Maity, Rahul; Bhosale, Rohit J.; Semwal, Divyam; Tothadi, Srinu; Vaidhyanathan, Ramanathan; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2021)
This note reports the synthesis and peptide formation of a novel triple G-C-T nucleobase amino acid (NBA) building block featuring three recognition faces: DDA (G mimic), DAA (C mimic), and ADA (T mimic). Readily obtainable in multigram scale in a remarkably easy one-step reaction, this unique NBA building block offers scope for wide ranging applications for nucleic acid recognition and nucleic acid peptide/protein interaction studies.

Creep resistance in doubly crosslinked dynamic covalent networks - Mondal, Swagata; Wong, Alexander J.; Wagh, Mahendra A.; Alperstein, Lily; Sanjayan, Gangadhar J.; Sumerlin, Brent S. (POLYMER CHEMISTRY, 2024)
Vitrimers are a unique class of thermosets that demonstrate reprocessability and recyclability due to dynamic bond exchange at crosslinking sites. However, the same dynamic bond exchange predisposes vitrimers to macroscopic deformation and creep under constant stress, which limits many practical applications. Herein, we demonstrated that the incorporation of Janus-faced guanine-cytosine diamine (GCBDam) functionality within vinylogous urethane vitrimers leads to significant creep resistance due to network reinforcement via hydrogen bonding. The supramolecular associations of the GCBDam groups retarded stress relaxation at temperatures as high as 160 degrees C. Further, rheological data suggested that the cooperative nature of the bifunctional Janus-faced hydrogen bonding moieties allowed the GCBDam to act as ``stickers'' within the dynamic covalent networks. These results indicate that incorporating the bifunctional supramolecular moiety improved dimensional stability while conserving the hallmark vitrimer property of reprocessability. This work demonstrates that incorporating Janus-faced supramolecular moieties in vinylogous urethane vitrimers improved dimensional stability while conserving the hallmark vitrimer property of reprocessability.

Dynamic janus hydrogen bond mimicry unlocks tough, flexible supramolecular elastomers for strain sensing - Lakshmi, Durga; Wagh, Mahendra A.; Sharma, Aakash; Alam, Md Shafi; Selvan, T. Muthamil; Torris, Arun; Mondal, Titash; Sanjayan, Gangadhar J.; Nair, Kiran Sukumaran (Chemistry of Materials, 2026)
Flexible and wearable electronics demand stretchable sensors with polymer elastomers as key matrixes for mechanical flexibility and durability. However, despite their excellent elasticity, their limited mechanical strength remains a challenge. To address this limitation, in this study, we report the rational design of supramolecular polyurethane elastomers (SPUs) incorporating nucleobase-inspired aminopyrimidinedione with DDA-AAD (G-C mimic) reversible triple hydrogen bonds. This dual-domain architecture gives rise to a durable supramolecular network with enhanced mechanical properties, yielding elastomers that are soft, stretchable, and tough. By tuning of the density of dynamic cross-links, mechanical properties were systematically modulated. SPU-0.5 exhibited a maximum tensile strength of 16.14 MPa, representing a 67-fold strength enhancement over that of SPU-0. Although increasing the aminopyrimidinedione (APD) content reduced elongation, SPU-0.2 retained a high elongation of 1060% and showed the lowest residual strain during cyclic tests. To be of great interest, the activation energy increased with increasing hydrogen bonding content up to SPU-0.1, whereas beyond SPU-0.2 it decreased, likely due to extensive hydrogen bond formation. Furthermore, SPU-0.2-SP, a conductive variant, demonstrated a promising strain-sensing performance even after hundreds of cycles. Overall, the insights gained from this study advance the development of intelligent soft materials and lay the groundwork for next-generation flexible and wearable electronic devices.